Structural and functional disconnections in non-acute post-stroke patients - Wu, Yanan; Tian, Chuanshuai; Yu, Zhixuan; Liu, Zaixing; Wu, Han; Ming, Jie; Hong, Wenjun; Xu, Rong (Frontiers in Neurology, 2025)
BackgroundStructural alterations and functional reorganizations related to motor dysfunction after stroke remain unclear. This study aims to investigate alterations in structural connectivity (SC) and functional connectivity (FC) in non-acute post-stroke patients, and their associations with motor performance.MethodsThirty-six non-acute post-stroke patients and thirty-eight well-matched healthy controls (HCs) were included. SC and FC differences between groups were analyzed using diffusion tensor imaging and resting-state fMRI, respectively. Correlations between SC and FC in regions with significant intergroup differences, along with their correlations with motor performance, were assessed.ResultsCompared with HCs, significant decreases in both SC and FC were observed in stroke patients among the right precentral gyrus, right superior frontal gyrus, right supplementary motor area, right paracentral lobule, right middle cingulate gyrus, right superior marginal gyrus, right middle temporal gyrus, and left inferior temporal gyrus. A negative correlation of SC-FC was found between the right middle cingulate gyrus and right paracentral lobule in stroke group, while a positive correlation was found between the right superior marginal gyrus and right middle temporal gyrus. Moreover, the FC between the right superior marginal gyrus and right middle temporal gyrus showed negative correlations with the Fugl-Meyer assessment of the Upper/Lower Extremity scores.DiscussionThis study identified disconnections in both SC and FC in sensorimotor-related and high-order brain regions, which may enhance understanding of the structure–function interactions underlying motor deficits in post-stroke patients.